Erratum to `Tuberculosis risk in the biologic era: tuberculin skin test conversion rates in children with rheumatologic diseases` [Turk J Pediatr 2021; 63: 978-985] - Özlü, Canan; Türkuçar, Serkan; Asrak, Hatice Karaoğlu; Dündar, Hatice Adıgüzel; Ünsal, Şevket Erbil; Belet, Nurşen (The Turkish Journal of Pediatrics, 2022)
This article is corrected. DOI: 10.24953/turkjped.2021.06.005.